Want this question answered?
Be notified when an answer is posted
2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.
2ab - 6ac + 3b - 9c = b(2a + 3) - 3c(2a + 3) = (b - 3c)(2a + 3)
n(2a - b)(2a + b)(4a^2 - 2ab + b^2)(4a^2 + 2ab + b^2)
2a+(-11b)
3(a + b) + a = 3a + 3b + a = 4a + 3b
2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.
5ab-2ab+4a-b+5b = 3ab+4a+4b
(4a - 3b)(4a + 3b)
Well, darling, to simplify 4a times 3b, you just multiply the numbers together to get 12, and then slap those variables together to get 12ab. It's as easy as making a martini on a Sunday afternoon. Cheers!
n(2a - b)(2a + b)(4a^2 - 2ab + b^2)(4a^2 + 2ab + b^2)
The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3
2ab - 6ac + 3b - 9c = 2a(b - 3c) + 3(b - 3c) = (2a + 3)(b - 3c).
2ab - 6ac + 3b - 9c = b(2a + 3) - 3c(2a + 3) = (b - 3c)(2a + 3)
4a+3b can not be algebraically simplified. It can be evaluated if you assign values to a and b.
n(2a - b)(2a + b)(4a^2 - 2ab + b^2)(4a^2 + 2ab + b^2)
= 4a2 + 2ab 2b2
2a+(-11b)